2007
DOI: 10.1007/s00027-007-0930-1
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate and microbial responses to inundation in an ephemeral river reach in New Zealand: effects of preceding dry periods

Abstract: Inundation marks the shift from a terrestrial ecosystem to an aquatic ecosystem in ephemeral rivers. The forms and rates of responses by aquatic invertebrates and sediment microbes to inundation depend on desiccation resistance during preceding dry periods. We assessed invertebrate and microbial responses to inundation over a range of preceding dry periods in an ephemeral reach of the Selwyn River, New Zealand. Microbial response variables were dissolved oxygen consumption and non-specific esterase activity. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(122 citation statements)
references
References 55 publications
6
112
3
1
Order By: Relevance
“…Declines in the diversity and abundance of invertebrates emerging from sediments as the duration of drying increases have been observed in several studies (e.g. Larned et al 2007;Datry et al 2012). Also, Jenkins and Boulton (2007) found that for microinvertebrate egg banks, drying for a period greater than 10-20 years resulted in marked declines in species richness.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Declines in the diversity and abundance of invertebrates emerging from sediments as the duration of drying increases have been observed in several studies (e.g. Larned et al 2007;Datry et al 2012). Also, Jenkins and Boulton (2007) found that for microinvertebrate egg banks, drying for a period greater than 10-20 years resulted in marked declines in species richness.…”
Section: Introductionmentioning
confidence: 78%
“…Decanting was repeated at days 20 and 30. A 30 day duration was chosen as sufficient to stimulate hatching and emergence in most species, based on similar studies (Jenkins and Boulton 2007;Larned et al 2007;Chester and Robson 2011;Datry et al 2012). These studies all used similar methods of inundation with non-chlorinated water, decanting and filtering with the exception that, as in Jenkins and Boulton (2007), samples were not aerated because the sediments were from lentic rather than lotic habitats.…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…Despite recent progress in understanding the role of dry channels as important habitats for terrestrial arthropods (e.g. Wishart, 2000;Larned et al, 2007;Steward et al, 2011;Steward et al, 2012;Corti and Datry, 2015;Corti et al, 2013;Corti and Datry, 2014), the terrestrial phase is not yet integrated into bioassessment strategies. We also need to consider the entire hydrological cycle in order to allow a more comprehensive assessment of the ecological status of Mediterranean NPRS .…”
Section: Biological Research Challengesmentioning
confidence: 99%
“…Such effects are partly explained by changes in abiotic processes driving LLD, including leaching of soluble compounds and physical abrasion (BĂ€rlocher, 1992). However, the most critical aspect of emersion periods lies in the physiological stress and spatial confinement (i.e., humid sediment patches and leaf litter refuges (Amalfitano et al, 2007 andYlla et al, 2010)) imposed on aquatic organisms that results in marked changes in the community structure and activity dynamics of microbial decomposers and invertebrate detritivores (Larned et al, 2007, Datry, 2012and Foulquier et al, 2015. Moreover, terrestrial invertebrates colonizing the river during droughts (Adis andJunk, 2002 andDatry, 2016) can eventually outcompete strictly aquatic organisms and modify the decomposition of leaf litter accumulated in dry river beds.…”
Section: Introductionmentioning
confidence: 99%